2017
DOI: 10.1590/1519-6984.166671
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of the Trichogramma endosymbiont Wolbachia, an alpha-proteobacteria (Rickettsiae)

Abstract: Wolbachia (Hertig) endosymbionts are extensively studied in a wide range of organisms and are known to be transmitted through the egg cytoplasm to the offsping. Wolbachia may cause several types of reproductive modifications in arthropods. In Trichogramma species, parthenogenesis-inducing Wolbachia bacteria allow females wasps to produce daughters from unfertilized eggs and these bacteria are present in at least 9% of all Trichogramma species. Phylogenetic studies have led to the subdivision of the Wolbachia c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…The thickness of the exine in the grains was lower in ‘Laszka’, ‘Radziejowa’, ‘Pokusa’, and ‘Polka’ were close to the values, but in the case of ‘Polana’ it was in the range of values determined in other Rubus species (0.9–2.4 μm) [ 64 , 73 , 74 , 78 , 79 , 105 ]. Sporopollenin contributes to high exine stability.…”
Section: Discussionsupporting
confidence: 68%
“…The thickness of the exine in the grains was lower in ‘Laszka’, ‘Radziejowa’, ‘Pokusa’, and ‘Polka’ were close to the values, but in the case of ‘Polana’ it was in the range of values determined in other Rubus species (0.9–2.4 μm) [ 64 , 73 , 74 , 78 , 79 , 105 ]. Sporopollenin contributes to high exine stability.…”
Section: Discussionsupporting
confidence: 68%
“…The intracellular symbiotic bacteria, Wolbachia , is a type of sex regulatory element that is ubiquitous in arthropods. Wolbachia can induce insects to undergo parthenogenesis (PI), cytoplasmic incompatibility, male-killing, and feminization (Werren & Windsor, 2000; Almeida & Stouthamer, 2018). The sex determination mechanism for Trichogramma is haplodiploidy, where fertilized eggs develop into diploid females and unfertilized eggs develop into haploid males (Perlman, Kelly & Hunter, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The Wolbachia -mediated phenotype are closely related with Wolbahcia titers. Many studies revealed Wolbachia were sensitive to multiple factors (e.g., temperature and antibiotic treatment) (Tulgetske & Michelle, 2010; Tulgetske & Stouthamer, 2012; Almeida & Stouthamer, 2018). The reduction of Wolbachia titers was often reported in high temperature (Zchori-Fein, Gottlieb & Coll, 2000; Ma & Schwander, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The intracellular symbiotic bacteria, Wolbachia, is a type of sex regulatory element that is ubiquitous in arthropods. Wolbachia can induce insects to undergo parthenogenesis (PI), cytoplasmic incompatibility(CI), male-killing(MK), and feminization (Werren & Windsor, 2000;Almeida & Stouthamer, 2018). The sex determination mechanism for Trichogramma is haplodiploidy, where fertilized eggs develop into diploid females and unfertilized eggs develop into haploid males (Perlman et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies revealed Wolbachia were sensitive to mutiple factors (e.g. temperature and antibiotic treatment) (Tulgetske et al, 2010;Tulgetske et al, 2012;Almeida & Stouthamer, 2018). The reduction of Wolbachia titers was often reported in high temperature (Zchori-Fein et al, 2000;Ma & Schwander, 2017).…”
Section: Introductionmentioning
confidence: 99%